2015
DOI: 10.4103/2277-9175.167030
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of intravenous dexamethasone, intravenous ondansetron, and their combination on nausea and vomiting in cesarean section with spinal anesthesia

Abstract: Background:Nausea and vomiting are frequently seen in patients undergoing cesarean section (CS) under regional anesthesia. We aimed to compare the antiemetic efficacy of ondansetron and dexamethasone combination with that of the use of each agent alone to decrease the incidence of postdelivery intra- and post-operative nausea and vomiting during CS under spinal anesthesia.Materials and Methods:A randomized, prospective, double-blind study was performed on 90 patients undergoing planned CS under spinal anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…They showed that intraoperative nausea was higher among patients treated with dexamethasone and lesser in patients who received their combination. But PONV was similar between the groups (23). Although the antiemetic effects of dexamethasone are well shown, the underlying mechanism of it is largely unknown (14).…”
Section: Discussionmentioning
confidence: 90%
“…They showed that intraoperative nausea was higher among patients treated with dexamethasone and lesser in patients who received their combination. But PONV was similar between the groups (23). Although the antiemetic effects of dexamethasone are well shown, the underlying mechanism of it is largely unknown (14).…”
Section: Discussionmentioning
confidence: 90%
“…The guidelines for PONV have been updated based on many clinical studies [ 5 , 6 ]. 5-HT 3 receptor antagonists, including ondansetron, are the gold standard antiemetics [ 7 , 8 ], and NK-1 receptor antagonists are also reported to be as effective as 5-HT 3 receptor antagonists [ 9 , 10 ]. However, 5-HT 3 and NK-1 receptor antagonists have not been approved for routine use by the Japanese Ministry of Health, Labor and Welfare as part of the public medical insurance coverage for perioperative antiemetics due to high cost.…”
Section: Resultsmentioning
confidence: 99%
“… 34 , 35 Drugs from different classes seem to complement each other concerning their antiemetic effects. 36 …”
Section: Discussion: Current Guidelines and Literaturementioning
confidence: 99%
“… 41 However, it may be considered for combination prophylaxis in conjunction with another drug with a different receptor profile. 40 Sane et al 36 published results of a randomized, prospective, double-blinded study in 2015. The trialists included 90 parturients undergoing elective CS with SPA and investigated the effectiveness of ondansetron 4 mg or dexamethasone 8 mg or a combination of both drugs.…”
Section: Discussion: Current Guidelines and Literaturementioning
confidence: 99%